The Blossom sisters - Michaels, Fern (Kensington Publishing Corporation, 2013)
Swindled out of his home by his gold-digging wife, successful accountant Gus Hollister returns to his grandmother Rose's Virginia farmhouse where he helps the residents of Blossom Farm expand their business and finds the courage to love again.